Grain Growth of Wheat Under Prevailing Air Temperature (Bangladesh Agronomy Journal, 2017)
An experiment was conducted at the Regional Agricultural Research Station, Ishwardi, Pabna in two consecutive years of 2010-2011 and 2011-2012 to quantify the effect of temperature on phenological duration and grain growth of wheat. Temperature variation was created by changing sowing date (15 November=S1, 30 November=S2, 15 December=S3 and 30 December=S4). Results revealed that reproductive phase was more sensitive to high temperature as compared to vegetative phase of wheat. Reproductive phase reduced from 54 to 37 days in 2010-2011 and from 64 to 34 days in 2011-2012 as influenced by higher air temperature under late sowing. Duration of reproductive phase was strongly and negatively correlated with mean air temperature (r=-0.64 to -0.96 at p